Crime and intelligence analysis an integrated real-time approach - Grana, Glenn; Windell, James O. (Routledge Taylor & Francis Group, 2021)
Crime and Intelligence Analysis: An Integrated Real-Time Approach, 2nd Edition, covers everything crime analysts and tactical analysts need to know to be successful. Providing an overview of the criminal justice system as well as the more fundamental areas of crime analysis, the book enables students and law enforcement personnel to better understand criminal behavior, learn the basics of conducting temporal analysis of crime patterns, use spatial analysis to better understand crime, apply research methods to crime analysis, and more successfully evaluate data and information to help predict criminal offending and solve criminal cases. A new chapter provides expert advice about terrorist threats and threat assessment. Criminal justice and police academy students, as well as civilians, sworn officers, and administrators, can build the skills to be credible crime analysts who play a critical role in the daily operations of law enforcement.